2008
DOI: 10.1007/s11332-008-0056-4
|View full text |Cite
|
Sign up to set email alerts
|

Postural control modifications induced by synchronized ice skating

Abstract: Some papers investigated the effects of specialized trainings on postural control adaptation. Particularly, several studies have been performed in ballet dancers. To our knowledge postural control in ice skaters, in general, has not yet been studied. Synchronized skating is an internationally recognized form of figure skating in which a team of 16 athletes, usually female, skate together. Similarities exist between the training regimens of synchronized skaters and ballet dancers with the major difference being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…Overall, these studies have demonstrated the trainability of three separate balance regulation systems, any of which could explain the results of the present study. Similar results have been observed with synchronized figure skaters, who did not have significantly better balance than control participants during quiet standing on a firm surface with eyes open (12).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Overall, these studies have demonstrated the trainability of three separate balance regulation systems, any of which could explain the results of the present study. Similar results have been observed with synchronized figure skaters, who did not have significantly better balance than control participants during quiet standing on a firm surface with eyes open (12).…”
Section: Discussionsupporting
confidence: 86%
“…Figure skaters had better balance than control participants when standing on a pliant surface which caused postural disturbances (12). Additionally, figure skaters demonstrated better weight distribution when standing on a pliant surface, which was thought to reproduce the unsteady condition of skates on ice (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicate that balance is one of the basic physical qualities of the athlete's execution of any sports movement, and if the athlete is to lose his balance abilities, he consequently loses his accuracy of performing the skill (Fong & Fong, 2012;Zemkova, 2011). Literature reviews show that are some sports that requiring fine postural control such as: gymnastics (Boso & Golias, 2012;Shigaki et al, 2013;Vuillerme, 2001), dance (Hatzitaki et al, 2002;Schmit, Regis & Riley, 2005) judo (Paillard et al, 2002;Perrin et al, 2002), fencing and shooting (Zemkova, 2011;Herpin et al, 2010), soccer (Jakobsen et al, 2011,Paillard et al, 2006, ice skating (Alpini et al, 2008), tai chi (Fong & Ng, 2006), and other sports (Schmit, Regis & Riley, 2005). Most of these studies were based on a kinetic analysis of the pressure exerted on different surfaces such as normal surface or foam surface, with sway support or reduced support on one or both legs, in different conditions, such as with eyes open and eyes closed.…”
Section: Introductionmentioning
confidence: 99%
“…Some papers investigated the evaluation and rehabilitation of balance disorders [2][3][4][5]. Some papers investigated the effects of specialized trainings on postural control adaptation [6][7][8], such as Mulan, walking backwards, particularly, the effects of specialized trainings on the postural control adaptation of old people, while the research is still rare for athletes. In the balance training program and related research, it is a vague concept whether gender should be taken into account or not.…”
Section: Introductionmentioning
confidence: 99%